The effect of Training the Foot that is not Usually Used in the Skill of Running with the Ball by Football Players - Fouad, Bejboug; Al-Sheikh, Mohammed (Latakia University Journal -Medical Sciences Series, 2018)
The objective of this research was to identify the effect of training the foot, which is not usually used in the skill of running with the ball. For this purpose, a training program was designed according to the scientific principles and it was nominated to the specialized experts. The sample consisted of (28) In the Syrian Arab Army Club, they ranged in age from 17-19 years. The experimental method was used in the two groups (experimental- regulatory). The experimental group underwent the training program, while the regulatory group was subjected to the regular trainer's program. the study showed a positive effect of the training program, and thus a development of the skill of running with the ball with the foot which is not marked by the usual use of members of the experimental group and the development of the performance of the foot which is characterized by the usual use in the skill of running with the ball as a result of the transfer of the training effect on the foot that is not marked by the usual use of the members of the experimental group. Therefore, we recommended that the training programs should be based on the scientific foundations of the specialists and trainers, and teaching and training the basic skills for both feet. أثر تدريب القدم غير المميزة بالاستخدام في مهارة الجري بالكرة لدى لاعبي كرة القدم هدف البحث إلى التعرف على أثر تدريب القدم غير المميزة بالاستخدام في مهارة الجري بالكرة لدى لاعبي كرة القدم الشباب، ولهذا الغرض تم تصميم برنامجٍ تدريبيٍ وفق الأسس العلمية وترشيحه على الخبراء و المختصين، وتكونت عينة البحث من (28) لاعباً من لاعبي فئة الشباب في نادي الجيش العربي السوري، تراوحت أعمارهم ما بين (17-19) سنة، وتم استخدام المنهج التجريبي بأسلوب المجموعتين المتكافئتين(تجريبية –الضابطة)، حيث خضعت المجموعة التجريبية للبرنامج التدريبي، بينما خضعت المجموعة الضابطة لبرنامج المدرب الاعتيادي،وتم استخدام اختبارٍ لقياس مهارة الجري بالكرة، وتم تطبيقه على القدم غير المميزة بالاستخدام قبل تطبيق البرنامج التدريبي وبعده على المجموعتين التجريبية والضابطة، وتم مقارنة النتائج بينهما، وتوصل البحث إلى تأثيرٍ إيجابيٍ للبرنامج التدريبي، وبالتالي تطور مهارة الجري بالكرة بالقدم غير المميزة بالاستخدام لدى أفراد المجموعة التجريبية، ومن هنا أوصينا بضرورة الاهتمام بوضع البرامج التدريبية المقننة التي تقوم على الأسس العلمية من قبل المختصين والمدربين، وتعليم وتدريب المهارات الأساسية التي تؤدى بالقدم في لعبة كرة القدم بالقدمين معا.